Adolescents with disabilities and caregivers experience of COVID-19 in rural Nepal - Morrison, Joanna; Poudyal, Niraj; Pun, Insha; Prasai, Sagar; Shrestha, Nir; Khadka, Dipesh; Shrestha, Sushmita; Rohwerder, Brigitte; Wickenden, Mary (Frontiers in Public Health, 2023)
Introduction: Intersecting vulnerabilities of disability, low socio-economic status, marginalisation, and age indicate that adolescents with disabilities in low-and middle-income countries were uniquely affected by the COVID-19 pandemic. Yet, there has been limited research about their experience. We conducted participatory research with adolescents with disabilities in rural, hilly Nepal to explore their experience of the pandemic and inform understanding about how they can be supported in future pandemics and humanitarian emergencies. Methods: We used qualitative methods, purposively sampling adolescents with different severe impairments from two rural, hilly areas of Nepal. We collected data through semi-structured interviews with five girls and seven boys between the age of 11 and 17 years old. Interviews used inclusive, participatory, and arts-based methods to engage adolescents, support discussions and enable them to choose what they would like to discuss. We also conducted semi-structured interviews with eleven caregivers. Results: We found that adolescents with disabilities and their families experienced social exclusion and social isolation because of COVID-19 mitigation measures, and some experienced social stigma due to misconceptions about transmission of COVID-19 and perceived increased vulnerability of adolescents with disabilities to COVID-19. Adolescents who remained connected with their peers throughout lockdown had a more positive experience of the pandemic than those who were isolated from friends. They became disconnected because they moved away from those they could communicate with, or they had moved to live with relatives who lived in a remote, rural area. We found that caregivers were particularly fearful and anxious about accessing health care if the adolescent they cared for became ill. Caregivers also worried about protecting adolescents from COVID-19 if they themselves got ill, and about the likelihood that the adolescent would be neglected if the caregiver died. Conclusion: Contextually specific research with adolescents with disabilities to explore their experience of the pandemic is necessary to capture how intersecting vulnerabilities can adversely affect particular groups, such as those with disabilities. The participation of adolescents with disabilities and their caregivers in the development of stigma mitigation initiatives and strategies to meet their needs in future emergencies is necessary to enable an informed and inclusive response.